Refugees in Tribal Global Village in Habiburahman and Mohsin Hamid - Karki, Aruna (Literary Studies, 2023)
In Habiburahman’s historical novel First, They Erased Our Name: A Rohingya Speaks and Mohsin Hamid’s Exit West, a semi-historical novel with elements of magical realism, I argue that refugees’ dream of global village or cosmopolis is constantly frustrated or deferred in a tribally oriented roadblocks of borders due to the nation-state’s sovereignty and its routine use of the state of exception; yet, these refugees do not give up their hope of founding a global village of sorts through the political space. To rephrase my claim, in these novels, the nation-state’s sovereignty, which exclusively reserves the prerogative of the state of exception, biopolitically forces a certain section of its people into bare life, in Agamben’s sense, forcing the refugees to flee their homelands and suffer during and after their numerous border crossings, denuding the presence of tribalism within the global village. Yet, largely owing to the occasional reception of individual hospitality, these refugees are able to keep alive their hope of belonging to a community through seeking the political, a space where they can negotiate and renegotiate their rights. I argue that their persecution is due to Myanmar’s military government’s biopolitics in that it has reinscribed the nation on the basis of religion and Sino-Tibetan race (tribalism) and rendered stateless the Rohingya Muslim of Indo-Aryan race. Nearly the same could be said about Hamid’s protagonists, Nadia and Saeed, as they face a similarly tribalistic predicament in London, where the city is divided between the dark and light zones, occupied by migrants and nativists, again the state siding with the nativist. Despite facing state brutality or state’s abdication of its responsibility and the absence of right to have rights, these refugees keep alive the hope of global village, and they are able to persevere because they do occasionally receive hospitality from a few good Samaritans; therefore, there remains some glimmering hope of cosmopolis or global village in an excessively tribalistic world they are forced to live, and it is this hope provides them energy to fight for their rights.